2016
DOI: 10.1523/jneurosci.0868-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Independent Causal Contributions of Alpha- and Beta-Band Oscillations during Movement Selection

Abstract: To select a movement, specific neuronal populations controlling particular features of that movement need to be activated, whereas other populations are downregulated. The selective (dis)inhibition of cortical sensorimotor populations is governed by rhythmic neural activity in the alpha (8 -12 Hz) and beta (15-25 Hz) frequency range. However, it is unclear whether and how these rhythms contribute independently to motor behavior. Building on a recent dissociation of the sensorimotor alpha-and beta-band rhythms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 58 publications
2
40
1
Order By: Relevance
“…A tACS-fMRI investigation revealed that the behavioral change was positively correlated with BOLD activity in primary motor cortex (M1) but it was negatively correlated with activity in dorsomedial prefrontal cortex, a region regarded as a locus of executive motor control (Moisa et al, 2016 ). Brinkman et al ( 2016 ) compared alpha and beta tACS to investigate movement selections. Enhanced movement acceleration and velocity were achieved with gamma band entrainment of the M1 (Moisa et al, 2016 ), and sensorimotor integration was promoted by beta band entrainment (Guerra et al, 2016 ).…”
Section: Target and Task-specific Tacsmentioning
confidence: 99%
“…A tACS-fMRI investigation revealed that the behavioral change was positively correlated with BOLD activity in primary motor cortex (M1) but it was negatively correlated with activity in dorsomedial prefrontal cortex, a region regarded as a locus of executive motor control (Moisa et al, 2016 ). Brinkman et al ( 2016 ) compared alpha and beta tACS to investigate movement selections. Enhanced movement acceleration and velocity were achieved with gamma band entrainment of the M1 (Moisa et al, 2016 ), and sensorimotor integration was promoted by beta band entrainment (Guerra et al, 2016 ).…”
Section: Target and Task-specific Tacsmentioning
confidence: 99%
“…Second, we considered the slope of the power-spectral density function (1/f slope), a summary index of synaptic excitation/inhibition balance (Gao et al, 2017). Furthermore, rather than assuming that alpha-and beta-band rhythms are spatially stationary across the sensorimotor cortex (Brinkman et al, 2016(Brinkman et al, , 2014, we examined the spatiotemporal distribution of the two sensorimotor rhythms and their cortical effects through two complementary analyses. First, we considered the organization of spatially systematic phase relationships among rhythmic signals (traveling waves) across the sensorimotor cortex (Ermentrout and Kleinfeld, 2001;Muller et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive brain stimulation methods such as transcranial alternating current stimulation (tACS) may offer a possibility to modulate neuronal oscillatory activity (for a review, see Herrmann et al, 2013 ) and human brain function in different modalities such as vision (Kanai et al, 2008 ; Laczó et al, 2012 ; Brignani et al, 2013 ; Helfrich et al, 2014a , b ; Cabral-Calderin et al, 2015 ; Vossen et al, 2015 ; Kasten et al, 2016 ; Vosskuhl et al, 2016 ), motor function (Pogosyan et al, 2009 ; Feurra et al, 2011a ; Schutter and Hortensius, 2011 ; Joundi et al, 2012 ; Brittain et al, 2013 ; Wach et al, 2013 ; Krause et al, 2014 ; Brinkman et al, 2016 ; Lustenberger et al, 2016 ; Moisa et al, 2016 ), audition (Neuling et al, 2012 ; Riecke et al, 2015 ; Heimrath et al, 2016 ; Riecke, 2016 ; Rufener et al, 2016 ), somatosensation (Feurra et al, 2011b ; Gundlach et al, 2016 ), and higher cognitive functions such as decision making, risk taking behavior, creativity, fluid intelligence, mental rotation or self-aware dreaming (Sela et al, 2012 ; Herrmann et al, 2013 ; Voss et al, 2014 ; Lustenberger et al, 2015 ; Santarnecchi et al, 2016 ; Kasten and Herrmann, 2017 ). In addition there is preliminary evidence that alternating current stimulation might be effective to support recovery of function in patients with stroke (Fedorov et al, 2010 ; Naros and Gharabaghi, 2017 ) or optic neuropathy (Sabel et al, 2011 ; Schmidt et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%